PERMAINAN TRADISIONAL LOMPAT TALI UNTUK MENGEMBANGKAN KEMAMPUAN FISIK MOTORIK KASAR PADA ANAK USIA DINI 5-6 TAHUN PAUD CAHAYA NUSANTARA - Jenah; Amat Hidayat; Beni Junedi (Jurnal Anak Bangsa, 2025)
This study aims to answer three research questions: (1) how the traditional jump rope game is implemented at PAUD Cahaya Nusantara, (2) how gross motor skills of children aged 5–6 years develop through the activity, and (3) what supporting and inhibiting factors affect its implementation. The study is based on the importance of gross motor stimulation in early childhood as the foundation for physical growth as well as social and emotional development. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The research subjects consisted of 15 children in group B, with supporting informants including the class teacher and the principal. The results showed that regular and structured jump rope activities improved children’s balance, coordination, physical endurance, and courage. Supporting factors included teacher creativity, adequate facilities, integration into the learning process, and parental support. Inhibiting factors included differences in children’s physical abilities, fear, limited playtime, and unfavorable weather conditions, which were overcome by adaptive teacher strategies. Thus, the jump rope game is an effective and enjoyable medium for developing gross motor skills in early childhood